Pengaruh Kualitas Sumber Daya Manusia dan Usia Usaha terhadap Kualitas Laporan Keuangan di Sektor Kuliner Kota Padang - Lestari, Dika; Umar, Desyani; Zulfia, Dewi; Rivandi, Muhammad (Magister Ilmu Akuntansi Universitas Jambi, 2026)
Small and Medium Enterprises (SMEs) play a strategic role as the backbone of the economy, driving economic growth and income equality, particularly in Padang City, which contributes significantly to the GRDP of West Sumatra Province. Despite their significant potential, SMEs still face fundamental challenges, particularly in preparing high-quality financial reports. The low quality of financial reports is caused by limited accounting knowledge, weak human resources (HR) quality, and a lack of business experience, as reflected in the age of the business. This study aims to analyze the influence of HR quality and business age on the quality of financial reports of culinary sector SMEs in Padang City. The method used is a quantitative approach with multiple regression analysis. The sample consisted of 60 fast food SMEs in Padang City in 2025. The results of this study indicate that human resources and business age have a positive and significant influence on the quality of financial reports in fast food SMEs in Padang City. This finding indicates the importance of increasing human resource capacity through training and mentoring, as well as business experience in supporting the preparation of more accurate, relevant, and reliable financial reports. This research is expected to be a basis for the government and related parties in designing policies and programs for empowering SMEs to improve the quality of financial reports and business competitiveness in a sustainable manner.